PENDIDIKAN DAN PEMBELAJARAN AL-QUR’AN DI SEKOLAH (LPPAIK Universitas Muhammadiyah Bandung, 2023)
This article discusses the education and teaching of the Qur’an in schools. In order to produce a generation that excels in ethics, akhlaqul karimah. So each school has different visions and missions, with these differences there is a common thread that can be applied simultaneously, namely the application of learning the Qur'an. This study will discuss the methods used in learning the Qur’an, common problems, and solutions to the problems of learning the Qur’an in schools. The model for writing this article is by using a descriptive-analytic methodology, based on library research. The results of this study are that there must be continuity between teachers, students, schools, parents, the environment, and their relatives. So that it will be born from every school of generations who have good morals with the basis of the Qur'an as a guide to their lives. It will also bring the souls of the students closer to the Qur'an, which is expected to bring peace, prosperity, and happiness not only in this world, but also in the hereafter.